Numerical study of the equation on the graph for the steady state non-Newtonian flow in thin tube structure - Kozulinas, Nikolajus; Panasenko, Grigory; Pileckas, Konstantinas; Šumskas, Vytenis (Mathematical Modelling and Analysis, 2023)
The dimension reduction for the viscous flows in thin tube structures leads to equations on the graph for the macroscopic pressure with Kirchhoff type junction conditions in the vertices. Non-Newtonian rheology of the flow generates nonlinear equations on the graph. A new numerical method for second order nonlinear differential equations on the graph is introduced and numerically tested.